Challenges of the digital transformation of microfinance in Peru - Toledo Concha, Emerson (2022)
The microfinance market in Peru, presents a marked supply of institutions. All of them, seek to increase their number of placements and deposits; and to achieve this, some institutions have made technological advances in terms of hardware or application development; however, others have adventured to explore how to design digital transformation programs. The objective of this research was to describe an exploration of information associated with digital transformation and tools that microfinance institutions must consider in order to go on this long path of transformation. The method used was based on a hermeneutic study, with a qualitative, exploratory, and descriptive approach, where several bibliographies from different electronic databases were consulted. It was concluded that carrying out a digital transformation in microfinance institutions is not just about digitizing manual procedures, or adding hardware or developing applications, but rather that the implementation strategy contains a transversal front and presents diverse elements such as: The incorporation of a digital culture throughout the institution, map credit processes and redesign them, focus the strategy applied to clients, and incorporate adequate digital tools and platforms to meet the objectives and business strategy. We believe that our results will serve as a basis for future research on this process of change in microfinance institutions.